Academic excellence as selection criteria among selected Malaysian employers - Hashim, Junaidah (2009)
This study examines the performance of employees as assessed by their supervisor. It tries to link a relationship between employees' performance with their academic excellence. It aims to measure the variables that could possibly influence employees' performance; such as job satisfaction, motivation and involvement in co-curriculum activities. Several instruments were used in this study. An adapted version of questionnaire used by Sarmiento, et al. (2007) was utilised to assess the perceived performance of employees. The subjects were evaluated by their immediate supervisor on a 6-poim scale. Ability construct was measured in terms of employee academic qualification and skills. A 13-item scale based on Porrer (1964) was used to measure motivation. A 14-item scale based on Hackman and Oldham's (1975) Job Diagnostic Survey was used to measure job satisfaction. The findings revealed that there is a weak relationship between employees' performance with CGPA. The findings also revealed that there is a low relationship between employees' performance and their job satisfaction, motivation and ability. The implications of the study are discussed.